Predicting Bleeding Risk by Platelet Function Testing in Patients Undergoing Heart Surgery. Issue 11 (8th October 2015) - Kuliczkowski, Wiktor; Sliwka, Joanna; Kaczmarski, Jacek; Zysko, Dorota; Zembala, Michal; Steter, Damian; Zembala, Marian; Fortmann, Seth; Serebruany, Victor
ABSTRACT: Background: Predicting bleeding events in patients with coronary artery bypass grafting (CABG) represents an unmet medical need that may improve CABG outcomes. Hypotesis: To assess the potential link between platelet function testing and bleeding risk in patients undergoing CABG. Methods: Platelet aggregation and clinical outcomes in 478 patients treated with aspirin and/or clopidogrel were retrospectively analyzed. Platelet activity was assessed prior to CABG with arachidonic acid (ASPI Test), and adenosine diphosphate(ADP Test) utilizing multiple‐electrode aggregometry. Results: In the study group of 478 patients, mean age was 65.2±15.2 years; 138 were women. The majority of patients (n = 198) underwent on‐pump surgery, with 162 undergoing off‐pump and 30 undergoing minimally invasive surgery. Forty‐eight patients received artificial valve implantation alone, and 40 received valve implantation in combination with CABG. The analysis of the entire pool revealed that an ASPI test value <407 area under curve per minute (AUC*min) may be useful in predicting postoperative drainage. In CABG patients only, an ASPI test value <271 AUC*min predicted the need for red blood cell concentrate transfusion following surgery. In patients who stopped clopidogrel for up to 5 days before surgery, the ADP test failed to exhibit prognostic utility for predicting bleeding risk. Conclusions: In patients undergoing heart surgery, an ASPI test value <407 AUC*min may predict higher postoperative drainage, whereas <271 AUC*min may be linked to postoperative use of red blood cell concentrate.